2020
DOI: 10.2196/18014
|View full text |Cite
|
Sign up to set email alerts
|

Health Gain, Cost Impacts, and Cost-Effectiveness of a Mass Media Campaign to Promote Smartphone Apps for Physical Activity: Modeling Study

Abstract: Background Physical activity smartphone apps are a promising strategy to increase population physical activity, but it is unclear whether government mass media campaigns to promote these apps would be a cost-effective use of public funds. Objective We aimed to estimate the health impacts, costs, and cost-effectiveness of a one-off national mass media campaign to promote the use of physical activity apps. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Specifically, smartphone ownership was higher than previously modeled and the reach of the mass media campaign was lower. We also conceptualized some of the pathway between the initial intervention (ie, the mass media campaign) to the effect size (ie, the effect of weight loss app use on BMI) based on new evidence that was incorporated into other modeling on mass media campaigns [ 37 ]. In our sensitivity analyses, we used the previously modeled effect size to isolate how much of a difference was due to the revised pathway versus the effect size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, smartphone ownership was higher than previously modeled and the reach of the mass media campaign was lower. We also conceptualized some of the pathway between the initial intervention (ie, the mass media campaign) to the effect size (ie, the effect of weight loss app use on BMI) based on new evidence that was incorporated into other modeling on mass media campaigns [ 37 ]. In our sensitivity analyses, we used the previously modeled effect size to isolate how much of a difference was due to the revised pathway versus the effect size.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that such a campaign was not cost-effective in the base case analysis [ 36 ]. Another study using similar methods assessed the potential of a mass media campaign to promote smartphone apps for physical activity and found that it was unlikely to be cost-effective at the population level, although the health impact and cost-effectiveness estimates were highly sensitive to assumptions around long-term adherence [ 37 ]. The evidence on the cost-effectiveness of mass media campaigns is primarily from tobacco control [ 29 ], and previous research indicates that a mass media campaign for promoting smoking cessation apps is likely to be cost saving [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence indicates that physical activity interventions would likely provide minimal chronic disease reduction benefits to adults aged <40 years in NZ [24,27]. Therefore, the age range for the intervention was restricted to 40 to 79 years.…”
Section: Intervention Specificationmentioning
confidence: 99%
“…When compared with selected health interventions in NZ, according to methodologically compatible modeling studies, we found that the prescription of smartphone apps for physical activity promotion in primary care was likely to provide larger health gains and cost savings for the health system than a mass media campaign for physical activity apps [27], a mass media campaign for weight loss apps [50], or weight loss counseling by nurses in primary care [51] in NZ (Table 6). However, the intervention was less effective than a mass media campaign to promote a smoking cessation app in NZ [52].…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…the top 2% reporting more than 500,000 monthly active users (MAUs) [ 25 ]). Unlike previous cost-effectiveness analyses of physical activity interventions more broadly (outside the mHealth context e.g., mass media campaigns), [ 26 28 ] analyses should model risk reductions based on objectively-measured (vs. subjective measures) and longer-term (6+ months, the theoretical threshold for behaviour maintenance) [ 29 ] changes in physical activity [ 19 , 20 , 30 ]. Age- and sex-specific models should also be used since disease incidence and mortality rates vary widely by demographic group [ 19 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%